Clinical practice recommendations for recurrence of focal and segmental glomerulosclerosis/steroid-resistant nephrotic syndrome - Weber, Lutz T.; Tönshoff, Burkhard; Grenda, Ryszard; Bouts, Antonia; Topaloglu, Rezan; Gülhan, Bora; Printza, Nikoleta; Awan, Atif; Battelino, Nina; Ehren, Rasmus; Hoyer, Peter F.; Novljan, Gregor; et al. (Pediatric transplantation, 2021)
Recurrence of primary disease is one of the major risks for allograft loss after pediatric RTx. The risk of recurrence of FSGS/SRNS after pediatric RTx in particular can be up to 86% in idiopathic cases. There is a need for consensus recommendations on its prevention and treatment. The CERTAIN study group has therefore performed a thorough literature search based on the PICO model of clinical questions to formulate educated statements to guide the clinician in the process of decision-making. A set of educated statements on prevention and treatment of FSGS/SRNS after pediatric RTx has been generated after careful evaluation of available evidence and thorough panel discussion. We do not recommend routine nephrectomy prior to transplantation; neither do we recommend abstaining from living donation. Special attendance needs to be given to those patients who had already experienced graft loss due to FSGS/SRNS recurrence. Early PE or IA with or without high-dose CsA and/or rituximab seems to be most promising to induce remission. The educated statements presented here acknowledge that FSGS/SRNS recurrence after pediatric RTx remains a major concern and is associated with shorter graft survival or even graft loss. The value of any recommendation needs to take into account that evidence is based on cohorts that differ in ethnicity, pre-transplant history, immunosuppressive regimen, definition of recurrence (eg, clinical and/or histological diagnosis) and treatment modalities of recurrence.